Arms From the Sea - Shapero, Rich; Von Bruenchenhein, Eugene, 1910-1983 (Half Moon Bay, California : TooFar Media, 2016)
"Lyle is a young man who hates his life in the State of Salt, a cultural and literal desert. He vandalizes a State icon, then swallows a poison pill that transports him not to death, but to a liminal realm - blue, watery, and wholly alien. Hes rescued and shepherded by henchmen of the Polyp, god of the oceanic world they call "heaven". A series of encounters unfolds between Lyle and the monstrous, seductive god, who gradually reveals his grandeur and mysterious purpose. Lyle is horrified at first but soon finds himself falling for the Polyp, and the potent and bizarre creative potential he represents. Whimsical and outlandish but also timely and dead serious, Arms from the Sea navigates imagined realms of possibility, pointing to what it might mean to redeem a desolate world" --Dust jacket
These arms
"Arms from the Sea is the fourth release from Library Journal acclaimed author, Rich Shapero, and is a novel enhanced with original music and fine art. The result is a fully immersive storytelling experience"--Letter from publisher
"Arms from the Sea combines Rich Shaperos fantastical novel with music by Orenda Fink and the visionary art of Eugene Von Bruenchenhein to create an other-worldly, immersive story experience"--Publisher
Keywords: Imagination -- Fiction; Gods -- Fiction; Action and adventure fiction; Fiction; Action and adventure fiction; Sea stories; Sea adventure fiction